Respuesta :
Here , we need to find an formula for nth term of the sequence 26 , 35 , 44 , .....
Now , here if you notice carefully ,then you can notice that 35 - 26 = 9 , 44 - 35 = 9 , So the given sequence is an AP ( Arithmetic Progression ) with common difference being 9 , first term being 26 , so now as we knows that :
- [tex]{\boxed{\bf{a_{n}=a+(n-1)d}}}[/tex]
Where , [tex]{\bf{a_n}}[/tex] is nth term of AP , [tex]\bf a[/tex] being first term while [tex]\bf d[/tex] is the common difference . So , now putting the values in above formula ;
[tex]{:\implies \quad \sf a_{n}=26+(n-1)9}[/tex]
[tex]{:\implies \quad \sf a_{n}=26+9n-9}[/tex]
[tex]{:\implies \quad \bf \therefore \quad \underline{\underline{a_{n}=9n+17}}}[/tex]
Henceforth , nth term of the sequence is 9n+17
Answer:
[tex]a_n=9n+17[/tex]
Step-by-step explanation:
From inspection we can see that the sequence is an arithmetic sequence since the common difference between terms is constant.
General form of an arithmetic sequence formula: [tex]a_n=a+(n-1)d[/tex]
(where a is the first term and d is the common difference).
To find the common difference subtract one term from the next:
[tex]d = 44-35=9[/tex]
or [tex]d=35-26=9[/tex]
Given:
- [tex]a=26[/tex]
- [tex]d=9[/tex]
Therefore, [tex]a_n=26+(n-1)9[/tex]
Simplified: [tex]a_n=9n+17[/tex]